Prevalence of Coccydynia Among Postpartum Women: Prevalence of Coccydynia Among Postpartum Women - Arif, Abida; Sardar, Soha; Farah Gilani, Maymoonah; Muneer, Rashida; Naz, Aqsa; Manzoor, Nosheen; Kashif, Muhammad (Pakistan Journal of Health Sciences, 2022)
Coccydynia is a painful condition of the coccyx that can have various etiologies. Females are affected five times more than males by this condition. In addition to being chronic and difficult to manage, its symptoms can be detrimental to quality of life. Objective: To determine the prevalence of coccydynia among postpartum women. Methods: In this study, 881 postpartum women were selected through non probability convenience sampling from obstetrics and gynecology ward of Allied Hospital, Faisalabad. Self-structured questionnaire was used which contains different sections; section 1 contains Demographic information of the participants; section 2 contains subjective and Objective assessment. Two tests straight leg raise and per rectal were performed confirm coccydynia. SPSS version 21.0 were used to enter and analysis the data. Results: Test According to SLR test, 396(45%) were positive and 485(55%) were negative in SLR test. According to PR test, 538(61%) were positive and 343(39%) were negative in PR test. The finding of the study shows that 538(61%) postpartum females have coccydynia. A significant relationship was found between Coccydynia and the method of delivery (p<.005), position with less pain (p<.001), and intensity of pain (<p.001). Conclusions: Coccydynia is most commonly found in postpartum women based on the results of this study. Coccydynia was also significantly associated with the method of delivery, the position with less pain, and the intensity of the pain during childbirth